The TLT Group - the Teaching, Learning and Technology affiliate of the American Association of Higher Education (AAHE). - Ron Thomas (Journal of Applied Communications, 2000)
A review of the organization the TLT Group - the Teaching, Learning and Technology affiliate of the AmericanAssociation of Higher Education (AAHE), Steven W. Gilbert, President.